Microbial community function in the bleaching disease of the marine macroalgae Delisea pulchra. (11th May 2017) - Zozaya‐Valdés, Enrique; Roth‐Schulze, Alexandra J.; Egan, Suhelen; Thomas, Torsten
Summary: Disease is increasingly viewed as a major factor impacting the health of both natural and cultured populations of marine organisms, including macroalgae. The red macroalga Delisea pulchra suffers from a bleaching disease resulting from host stress and infection by opportunistic bacterial pathogens. However, how pathogens cause the disease and how the entire macro algal‐associated community is involved in the process is unclear. Here, we perform a metagenomic analysis of microbial communities associated with diseased and healthy D. pulchra across multiple bleaching events. Analysis of reconstructed 16S rRNA gene sequences showed that bacteria belonging to the families Rhodobacteraceae, Saprospiraceae and Flavobacteriaceae, including bacteria previously implicated in algal bleaching, to be enriched in diseased D. pulchra . Genes with predicted functions related to chemotaxis, motility, oxidative stress response, vitamin biosynthesis and nutrient acquisition were also prevalent in microbiomes of bleached algae, which may have a role in pathogenicity. Reconstruction of genomes that were abundant on bleached samples revealed that no single organism contains all bleaching‐enriched functional genes. This observation indicates that potential virulence traits are distributed across multiple bacteria and that the disease in D. pulchra may result from a consortium of opportunistic pathogens, analogous to dysbiotic or polymicrobial diseases.